Optimalisasi Penerapan Five Moment Hand Hygiene pada Staf Puskesmas Pematang Tiga - Harsismanto J; Elisa Fitriana Handayani; Padila Padila; Juli Andri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to optimize the application of five-moment hand hygiene for the Pematang Tiga Health Center staff. This research method uses a quantitative methodology with a quasy experiment, one group pre-test, and a post-test design approach. The results showed that the average score of staff knowledge related to five moments of hand hygiene before the intervention was 67.50, or in the excellent category. The bivariate analysis of the two data using the Paired sample t-test showed a value of p = 0.000 <0.05. In conclusion, there is a difference in the average score of staff knowledge related to five-moment hand hygiene before and after giving the intervention. Keywords: Five Moments of Hygiene, Staff